(NiSSLEDOWANIE OPERACIJ W ZADA^AH I UPRAVNENIQH (B:s (Nu^EBNOE POSOBIE (B/s - (NmOROZOW(B, (NwLADIMIR wIKTOROWI^s; (NsUHAREW(B, (NaLEKSEJ gRIGORXEWI^s; (NfEDOROW(B, (NwQ^ESLAW wASILXEWI^s ((NmOSKWA (B:s (NwYS[AQ [KOLA(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 284-286 (72 (NNAZW(B.)s
Keywords: (NmATEMATIKAs; (NoPERACIJ ISSLEDOWANIE (B((NMAT(B.)s